Quantum Fields and Off-Shell Sciences - Ohtsu, Motoichi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Intensive studies on light-matter interactions and technological breakthroughs, especially conducted in the field of dressed photon research, have led to a growing concern regarding unsettled off-shell quantum field interactions. The Special Issue, entitled "Quantum Fields and Off-Shell Sciences", was organized to promote the progress of such research activities from a wider perspective, not limited to dressed photon studies. This book contains excellent papers that were published in this Special Issue. It will provide scientific and technical information on the quantum fields and off-shell sciences to scientists, engineers, and students who are and will be engaged in this field.